A patient with oxaliplatin immune-induced syndrome (OIIS) who also developed leucovorin and palonosetron-associated thrombocytopenia. Issue 7 (9th August 2018) - Curtis, S. A.; Curtis, B. R.; Lee, A. I.; Hendrickson, J. E.; Lacy, J.; Podoltsev, N. A.
ABSTRACT: Objectives: We report a case of an 83 year old man who developed oxaliplatin immune-induced syndrome (OIIS) after his 19th cycle of FOLFOX (5FU, leucovorin, oxaliplatin). When oxaliplatin was omitted from his next cycle of chemotherapy he continues to show signs of drug-induced immune thrombocytopenia (DITP) and was found to have drug-dependent, platelet-reactive antibodies (DDPA) to leucovorin and palonosetron as well as oxaliplatin. Methods: The patient was admitted for monitoring but required no transfusions and thrombocytopenia resolved without treatment during his first admission. Drug-dependent antibody testing was performed on his blood by the Blood Center of Wisconsin (Diagnostic Laboratories; Milwaukee, WI). Results: No RBC or platelet IgG or IgM antibodies were detected in the absence of any drugs, but upon addition of palonosetron, leucovorin, or oxaliplatin, the tests became strongly positive for anti-RBC IgG and anti-platelet IgG antibodies. Discussion: Repeated administration of oxaliplatin can result in drug-induced immune thrombocytopenia (DITP) or autoimmune hemolytic anemia (AIHA). This phenomenon has recently been termed OIIS and may additionally include Evan's syndrome or thrombotic microangiopathy (TMA). Here we describe a patient who developed OIIS with drug-dependent, platelet-reactive antibodies (DDPA) to leucovorin and palonosetron. To our knowledge, these two drugs have never been described in the literature as a cause of DDPA. We suggest that OIIS in addition to oxaliplatin-induced thrombocytopenia may be associated with the development of DDPAs to other drugs causing clinically significant thrombocytopenia which is important to recognize and manage with discontinuation of provoking agents.